Circulating Immune Complexes and Complement Activation in Sensitized Kidney Transplant Recipients - Trivyza, Maria Stella; Stergiopoulou, Charikleia; Tsakas, Sotiris; Ntrinias, Theodoros; Papasotiriou, Marios; Karydis, Nikolaos; Papachristou, Evangelos; Goumenos, Dimitrios S. (International journal of molecular sciences, 2024)
Chronic antibody-mediated rejection in kidney transplantation is a common cause of graft loss in the late post-transplant period. In this process, the role of the classical complement activation pathway is crucial due to the formation of immune complexes between donor-specific antibodies (DSAs) and donor antigens and the attachment of the C1q complement fragment. This study aimed to determine the levels of circulating C1q immunocomplexes (CIC-C1q) and complement activation (CH50), in sensitized kidney transplant recipients (KTRs). In this cross-sectional study we used serum samples from KTRs with de novo or preformed DSAs (n = 14), KTRs without DSAs (n = 28), and 22 subjects with no history of chronic kidney disease (controls). C1q immunocomplexes and CH50 concentration in serum were measured with the enzyme immunoassay (EIA) kit MicroVue CIC-C1q (Quidel, Athens, OH, USA) and EIA kit MicroVue CH50 (Quidel, OH, USA), respectively. Higher concentrations of CIC-C1q was observed in KTRs with DSAs in comparison with controls and with KTRs with no DSAs (6.8 ± 2.7 and 4.8 ± 1.9 vs. 5.0 ± 1.2 μg Eq/mL, respectively, p < 0.01). We found no difference in CIC-C1q between KTRs with no DSAs and controls. CIC-C1q levels were positively correlated with DSA titer. CH50 levels were decreased in KTRs with DSAs in comparison with controls and KTRs with no DSAs (39 ± 15 vs. 68 ± 40 and 71 ± 34 U Eq/mL, respectively, p < 0.01). There was no difference in CH50 between DSA-negative KTRs and controls. Kidney transplant recipients with DSAs had increased serum levels of C1q immunocomplexes and increased classical pathway complement activation.